Review on Covid-19 Disease: Its Outbreak and Current Status - Pankaj Wagh1 , Saood Ali1 , Ulhas Jadhav2, Babaji Ghewade3 , Deepanshu Chawla4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Summary: Coronavirus (COVID-19) is diversely found in human beings and wild animals. It is an envelopedRNA virus. There are a total six species which cause disease in humans. They commonly infect respiratory,neurological, enteric, and hepatic systems. There is history of endemic outbreaks in past in the form ofMiddle East respiratory syndrome coronavirus (MERSCoV) and severe acute respiratory syndrome relatedcoronavirus (SARS-CoV).We have seen another outbreak due to a new strain called the SARS-CoV-2 viruswhich presented as a pneumonia of unknown etiology in patients in Wuhan,China. The epicenter of infectionwas linked to seafood and exotic animal wholesale markets in the city. It is highly contagious and hasresulted in a rapid pandemic of COVID-19. As the number of cases continue to rise, it is clear that theseviruses pose a threat to public health. This review will describe clinical features and treatment of COVID-19patients and raise awareness among healthcare workers and general population during the current pandemic.This review article aims at giving up-to-date information about the disease and counselling of patients.